Hubungan Self Efficacy dengan Perilaku Caring Perawat di Ruang Rawat Inap Rumah Sakit XX Palembang - Drama, Shelfi Meylani; Yulia, Sri; Muliyadi, Muliyadi (Jurnal Berita Ilmu Keperawatan, 2020)
Background: Nurses have a great effect in determining a service quality of a hospital.In particular, caring attitude of paying attention to patients in a humanistic manner will improve a harmonious relationship between nurses and patients. Self-efficacy is one of the factors influencing the caring attitude of a nurse. Objective: This study aimed tofind out the relationship between self-efficacy and caring attitude of the nurses of inpatient wards of BhayangkaraHospital of Palembang in 2017.Method: Thiswas a quantitative study using a correlative descriptive design with cross-sectional approach. The sampling technique was total sampling with the number of sample of 48 respondents. The data were collected using a questionnaire asking 32 items of caring statements and 26 items of self-efficacy statements.Results: Good caring nurses were 28 respondents (58.3%), while good self-efficacy of the nurses was 26 respondents (54.2%). The statistical test result showed that there was a relationship between self-efficacy and caring of the nurses (p Value = 0.05).Conclusion and Suggestion: The caring attitude of the nurses is very important in providing services to patients so that the caring attitude of each nurse can be improved and caring attitude can be cultivated when providing services. To improve self-efficacy can be done through training programs, reward, support, role model, or other specific strategies. Keywords : Self-efficacy, Caring Nurses